STRATEGI MEDIA SOSIAL DAN CREATIVE BRANDING BANYUMU DALAM MEMBANGUN BRAND AWARENESS - Ramadhan, Djuniawan (Jurnal Visi Komunikasi, 2020)
This project has the objective of building Brand Awareness of a newcomer brand, Banyumu. Has an innovative product, namely a dispenser machine that is integrated with the application (mobile app) to refill drinking water in a tumbler (drinking bottle). Banyumu is here to provide a solution to Green Consumers' concerns when they want to refill drinking water in their tumbler when they are outside, and also aims to reduce the use of disposable drinking bottles. Using the theoretical foundation of branding, advertising, digital marketing communications, Brand Awareness, creativity in advertising, big ideas, and Creative Directors. To build Brand Awareness, of course, a brand must have an identity to be more easily recognized or remembered by the target audiens, especially Banyumu is a new brand. The use of the Guerrilla Marketing concept on social media (digital media) as the main media with Green Consumers as the main target audiens who are 18-35 years old and live in urban areas, who are active and have flexibility in the digital world.Banyumu has become a Brand Recognition from the Unaware Brand stage, which now makes it easier to introduce and market its products to a target audience. Brand Identity / Brand Elements, Key Visual, Brand Persona, Social Media Account, and Social Media Ads are the result of design that can be used by Banyumu.